Prevalence of a minimal luminal cross sectional area of coronary arteries < 4 mm2 determined by intravascular ultrasound in patients with coronary artery calcium scores of 0-100, 100-200, 200-300, 300-400, and > 400 determined by cardiac computer tomography - Shao, John H.; Aronow, Wilbert; Ravipati, Gautham; Kalapatapu, Kumar; Weiss, Melvin B.; DeLuca, Albert J.; Monsen, Craig E.; Sorbera, Carmen; Belkin, Robert N.; Pucillo, Anthony L. (Archives of Medical Science, 2009)
Introduction: The prevalence of a minimal luminal cross sectional area (MLCSA) of coronary arteries < 4 mm 2 determined by intravascular ultrasound (IVUS) in patients with coronary artery calcium (CAC) scores determined by computer tomography (CT) needed investigation. Material and methods: We investigated the prevalence of a MLCSA of coronary arteries < 4 mm 2 determined by IVUS in patients with CAC scores of 0-100, 100-200, 200-300, 300-400, and > 400 determined by CT. The 25 patients included 16 men and 9 women, mean age 60 ±8 years, who had IVUS measurements of MLCSA of coronary artery lesions and of CAC score from the same coronary artery. A MLCSA of coronary arteries < 4 mm 2 determined by IVUS was considered significant coronary artery obstruction. A CAC score of 0-100 was considered mild coronary artery disease (CAD), of 100-400 moderate CAD, and of > 400 severe CAD. Results: The mean MLCSA was 5.2 mm 2 in patients with CAC scores of 0-100, 4.7 mm 2 in patients with CAC scores of 100-200, 4.2 mm 2 in patients with CAC scores of 200-300, 5.6 mm 2 in patients with CAC scores of 300-400, and 3.8 mm 2 in patients with CAC scores of > 400 (p not significant). A MLCSA < 4 mm 2 was present in 3 of 6 patients (50%) with CAC scores of 0-100, in 3 of 6 patients (50%) with CAC scores of 100-200, in 2 of 4 patients (50%) with CAC scores of 200-300, in 0 of 3 patients (0%) with CAC scores of 300-400, and in 4 of 6 patients (67%) with CAC scores > 400 (p not significant). Conclusions: These data indicate that CAC scores determined by CT do not accurately predict significant obstructive CAD determined by IVUS.